Modification of amorphous phase of semicrystalline polymers - Rozanski, A.; Galeski, A. (Polimery, 2012)
Routes of amorphous phase modification of several semicrystalline polymers, such as polypropylene, high density polyethylene and polyamide 6 were described. It appeared that amorphous phase alteration leads in each case to changes in tensile deformation of those polymers, especially cavitation. The reason is the modification of amorphous phase free volume: increase or decrease of the average size of free volume pores. The modification of the free volume of amorphous phase by introducing penetrants has been developed that affects the initiation and intensity of cavitation. Furthermore, the reasons for the yield stress decrease as a result of introducing low-molecular weight penetrator into pores of free volume of the amorphous phase were also described.